The Effect of Virtual Simulator Media on Solar System Learning Outcomes in Science Education - Kawakibi, M.Ahsanal; Hayati, Nur (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2026)
Science education in the 21st century faces significant challenges in delivering abstract concepts to students, particularly those requiring high spatial understanding and large-scale objects like the Solar System. Because these concepts are difficult to comprehend through conventional instructional methods, students often experience suboptimal learning outcomes. To address this limitation, interactive virtual simulators offer a solution to dynamically visualize these phenomena. This study investigates the effect of virtual simulator media in science learning on students’ learning outcomes, particularly on the solar system topic. A quasi-experimental nonequivalent control group design was employed, involving 36 seventh-grade students from SMPI Mbah Bolong Jombang. The experimental group (n=18) engaged in learning using interactive virtual simulators—Solar System Scope and Universe Sandbox—while the control group (n=18) received conventional instruction. The results showed a significant improvement in the experimental group’s learning outcomes, with an average increase of 19.4 points, compared to 12.8 points in the control group. The independent t-test indicated a significant difference between the two groups’ posttest scores (p = 0.014), confirming the effectiveness of virtual simulators in enhancing students’ cognitive achievement in complex science topics such as astronomy.